Measuring the extent to which Application the criteria Transfer stations (regularity) for the municipalities of Karrada and Shula (Journal of Planner and Development, 2023)
The process of transporting waste from urban areas to sanitary landfill sites requires large amounts of money due to the length and distance. To address this problem, temporary transfer stations were established by the Municipality of Baghdad to reduce the cost of transportation, and for the purpose of preserving the environment in a sustainable manner, standards were set for the establishment of these stations. The two stations of Al-Karrada Municipality and Al-Shula Municipality were chosen as a case study to measure the extent of adopting and applying the standards for establishing substations locally, regionally and internationally, and the most important results were reached Which is that the transforming (regular) stations of the two study areas do not conform to the standards of establishing stations by a large percentage, and the (toxic) waste juice is not treated safely. Also, the number of mechanisms (container crane) is not commensurate with the amount of waste arriving at the regular transfer stations of the municipalities of Karrada and Shula, which leads to the survival of waste for several days inside the station, which causes contamination of machinery and equipment and their erosion over time, which leads to their inefficiency. The research recommended applying and adopting standards for transformer stations to maintain a safe and sustainable environment. The number of mechanisms (container crane) should be increased in the regular transfer stations. The waste juice must be treated safely and transported by specialized mechanisms to the treatment site in Al Rustamiya.